Visual function and psychological variables in alcohol dependency syndrome. (3rd April 2021) - Poças, Ilda Maria; Grilo, Ana; Lino, Pedro; Cabrita, Ana; Carvalho, Ana; Ruivo, Claudia; Rocha, Raquel; Cairrão, Sara
ABSTRACT: Introduction: Alcohol Dependence Syndrome (ADS) is defined as excessive alcohol consumption accompanied by psychological, physical, social, and economic disorders. Alcohol consumption affects motor and proprioceptive functions, decreasing motor and cognitive functions and causing attention deficits. We aim to evaluate visual function and attention, and psychological profiles in consumer and abstainer ADS patients. Methods: This quantitative, descriptive, cross-sectional and correlational study evaluates visual function in a sample of ADS patients. The Portuguese version of the Brief Symptom Inventory was used to assess patients' psychological status. The orthoptic examination protocol for visual function consisted of 11 standardized tests: VA for distance and near, ocular movements, near convergence and accommodation point, cover and prismatic cover tests, fusional vergence for distance and near, near stereoacuity, chromatic vision, contrast sensitivity and visual attention. Results: The sample included 176 patients. 121 were consumers and 55 were abstainers, aged between 31 and 72. The most affected parameters of visual function were visual acuity (80.39%), contrast sensitivity (67.50%), convergence at distance (66.44%) and near stereopsis (62.75%). Visual function was impacted in both groups. Regarding psychological status, consumers had higher averages for the Depression subscale, followed by Paranoid Ideation and Obsession. Abstainers had the highest averages in the Obsession subscale, followed by Paranoid Ideation and Depression. Statistically significant differences existed between the groups in the subscales for depression (p=.046) and paranoid ideation (p =.042). Conclusion: Changes in visual function and attention, as well as psychopathological function, should be considered in the rehabilitation of ADS patients.